2017
DOI: 10.5194/wes-2017-22
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impacts of the Low-Level Jet's Negative Wind Shear on the Wind Turbine

Abstract: Abstract. Nocturnal Low Level Jets (LLJs) are defined as relative maxima in the vertical profile of the horizontal wind speed at the top of the stable boundary layer. Such peaks constitute major power resources for wind turbines. However, a wind speed maximum implies a transition from positive wind shears below the peak to negative ones above. The effect that such transition inflicts on wind turbines has not been thoroughly studied. High-frequency data of actual atmospheric LLJs were used as input to the NREL … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…12c). While previous work (Gutierrez et al, 2017) has found that negative shear can decrease loads on the wind turbine system (primarily at the nacelle and tower), the positive shear in these profiles has been directly linked to an increase in static and dynamic loads relative to a well-mixed profile (Gutierrez et al, 2016). A recent study (Gutierrez et al, 2019) investigated the symmetry in wind turbine loads when the rotor experiences half-positive and half-negative shear and found complex interplay between the tower, blades and gravitational loads.…”
Section: Low-level Jetsmentioning
confidence: 98%
See 2 more Smart Citations
“…12c). While previous work (Gutierrez et al, 2017) has found that negative shear can decrease loads on the wind turbine system (primarily at the nacelle and tower), the positive shear in these profiles has been directly linked to an increase in static and dynamic loads relative to a well-mixed profile (Gutierrez et al, 2016). A recent study (Gutierrez et al, 2019) investigated the symmetry in wind turbine loads when the rotor experiences half-positive and half-negative shear and found complex interplay between the tower, blades and gravitational loads.…”
Section: Low-level Jetsmentioning
confidence: 98%
“…When the nose of the jet is within the rotor-swept area, a portion of the rotor will experience negative shear. Here, we quantify how much of the rotor experiences negative vs. positive shear for each LLJ profile using the turbine-jet relative distance parameter (ξ ; Gutierrez et al, 2017Gutierrez et al, , 2019. These values are shown in Fig.…”
Section: Low-level Jetsmentioning
confidence: 99%
See 1 more Smart Citation
“…As depicted in Fig. 1, LLJs at, above and below these altitudes have the potential to impact the wind speed, turbulence and shear across typical wind turbine rotor planes, and analyses of both observational data and Weather Research and Forecasting (WRF) simulations indicate that LLJs frequently occur at heights that interact with the rotor plane (Gutierrez et al, 2014(Gutierrez et al, , 2017Nunalee and Basu, 2014;Wagner et al, 2019;Aird et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Low-level jets modify wind power performance and loading by impacting wake recovery rates and vertical profiles of wind speed, direction and turbulence (Wharton and Lundquist, 2012;Bhaganagar and Debnath, 2014;Park et al, 2014;Gutierrez et al, 2017). Thus, for a complete assessment of loads and power, it is important to have a broad understanding of the site-specific low-level jet characteristics: how often do they the spatial and temporal variability of the coastal jets we refer to Ranjha et al (2013) and Lima et al (2018), who presented global maps based on reanalysis data.…”
Section: Introductionmentioning
confidence: 99%